2023
DOI: 10.1111/gcbb.13025
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of different landrace and commercial sorghum (Sorghum bicolor (L.) Moench) straw varieties by anaerobic digestion

Abstract: To reduce the impact on the environment and enhance the sustainability of resources, it is necessary to promote and strengthen the use of landrace cultivars that advocate regenerative agriculture. In this study, the growth and development as well as the anaerobic digestion (AD) of six different landrace cultivars, two commercial hybrids cultivars and a public genotype of Sorghum bicolor have been evaluated. The landrace cultivars, in general, presented greater heights, biomass yields and compactness shoots as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…According to Holliger et al (2016) [23], the headspace depends on biogas measurement method (volumetric or manometric), ranging from 500 to 1000 mL. In the present review, it was found that the headspace ranges from 10 mL [84] to 1400 mL [67].…”
Section: Bmp Experimental Conditions and Resultsmentioning
confidence: 49%
“…According to Holliger et al (2016) [23], the headspace depends on biogas measurement method (volumetric or manometric), ranging from 500 to 1000 mL. In the present review, it was found that the headspace ranges from 10 mL [84] to 1400 mL [67].…”
Section: Bmp Experimental Conditions and Resultsmentioning
confidence: 49%